The Cult of Old Believers' Domestic Icons and the Beginning of Old Belief in Russia in the 17th-18th Centuries - Sulikowska, Aleksandra (Religions, 2019)
The aim of this paper is to present the cult of icons in the Old Believer communities from the perspective of private devotion. For the Old Believers, from the beginning of the movement, in the middle of the 17th century, icons were at the center of their religious life. They were also at the center of religious conflict between Muscovite Patriarch Nikon, who initiated the reforms of the Russian Orthodox Church, and the Old Believers and their proponent, archpriest Avvakum Petrov. Some sources and documents from the 16th and 18th centuries make it possible to analyze the reasons for the popularity of small-sized icons among priested (popovtsy) and priestless (bespopovtsy) Old Believers, not only in their private houses but also in their prayer houses (molennas). The article also shows the role of domestic icons from the middle of the 17th century as a material foundation of the identity of the Old Believers movement.